A comic-based approach to permission request communication. Issue 124 (January 2023) - Watson, Katie; Just, Mike; Berg, Tessa
Abstract: Text-based permission requests do little to engage and inform smartphone users. Comics have recently been used with permission requests, though only in a survey of participants' perceived reactions. In this paper we study more realistic reactions to comic-based and text-based permission requests. For our study, we invited participants to engage with a prototype version of a fictitious WebApp (PetConnect); participants were only informed of our intent to study permission requests at the end of the study. While using the app, participants were exposed to four permission request types (contact, storage, location and calendar) related to different functions of our app, using one of two styles of request (comic-based or text-based). Our results showed that participants were significantly more likely to deny the comic-based requests vs the text-based requests (47% vs 33%) and that comic-based requests were perceived to be more influential in participant decision making. Both styles of request were perceived to be equally relevant to the app, as well as equally annoying. We discuss several observations for future permission request design based on our participants' explanations of their choices.